2020
DOI: 10.1088/1361-6471/abb1f9
|View full text |Cite
|
Sign up to set email alerts
|

Application of artificial intelligence in the determination of impact parameter in heavy-ion collisions at intermediate energies

Abstract: The impact parameter is one of the crucial physical quantities of heavy-ion collisions, and can affect obviously many observables at the final state, such as the multifragmentation and the collective flow. Usually, it cannot be measured directly in experiments but might be inferred from observables at the final state. Artificial intelligence has had great success in learning complex representations of data, which enables novel modeling and data processing approaches in physical sciences. In this article, we em… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 81 publications
0
26
0
Order By: Relevance
“…It employs multiple layered Artificial Neural Networks to learn higher dimensional correlations in the data. Machine learning and Deep Learning methods have been widely used both in theory [34][35][36][37][38][39][40][41][42][43][44][45][46][47][48] and in experimental high energy physics [49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68]. Previous studies [18,20] on identifying the QCD phase transitions have shown that Convolutional Neural Network (CNN) based models can accurately classify the underlying equation of state from a hydrodynamic evolution using the p tφ spectra of pions (differential transverse and angular distributions in the transverse plane).…”
Section: Pointnet For Classifying the Eosmentioning
confidence: 99%
“…It employs multiple layered Artificial Neural Networks to learn higher dimensional correlations in the data. Machine learning and Deep Learning methods have been widely used both in theory [34][35][36][37][38][39][40][41][42][43][44][45][46][47][48] and in experimental high energy physics [49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68]. Previous studies [18,20] on identifying the QCD phase transitions have shown that Convolutional Neural Network (CNN) based models can accurately classify the underlying equation of state from a hydrodynamic evolution using the p tφ spectra of pions (differential transverse and angular distributions in the transverse plane).…”
Section: Pointnet For Classifying the Eosmentioning
confidence: 99%
“…Machine learning techniques are widely used in high energy physics, both in experiments and theory to develop models that can replace conventional analysis techniques . Naturally, such techniques have also been proposed as tool for impact parameter determination in [31][32][33][34][35][36]. However, previous studies were using shallow neural networks or other traditional Machine Learning algorithms with simplified experimental constraints based on detector acceptance and event selection.…”
Section: Introductionmentioning
confidence: 99%
“…For * huangxuguang@fudan.edu.cn heavy ion collisions, the impact parameter can be viewed as one of the IDs of an event. Several works have proved the effectiveness of DL methods on impact parameter 'recognition' [9][10][11][12][13][14][15][16][17]. From a simple neural network [9] to a PointNet model [13] and to boosted decision trees [17], with the development of machine learning algorithms, more and more appropriate learning methods have been proposed to improve the performance of 'recognition' and to satisfy experimental requests.…”
Section: Introductionmentioning
confidence: 99%
“…From a simple neural network [9] to a PointNet model [13] and to boosted decision trees [17], with the development of machine learning algorithms, more and more appropriate learning methods have been proposed to improve the performance of 'recognition' and to satisfy experimental requests. However, most of these researches only involve collisions at low or intermediate energies [9][10][11][12][13][14][15][16]. Though a recent work [17] considered LHC energies, the adopted machine learning model is not a deep neural network.…”
Section: Introductionmentioning
confidence: 99%